Investigating the Potential of the Community Management Plus Model for Governing Community Drinking Water Systems in Barind Tract of Bangladesh: A Case Study of Deep Tube- Well Water Supply Installations (Social Science Review, 2024)
Community Management Plus (CM+) has recently been promoted as a better alternative approach for governing community drinking water systems (CDWS) in Bangladesh and elsewhere in the global south. However, it is still largely unearthed under what condition this model is likely to work for ensuring the sustainable performance of CDWS. The study, therefore, aims to explore the conditions that are likely to explain variation in the occurrence of the CM+ model in the Northwestern Barind Tract of Bangladesh. The study employed a case study approach where a deep tube-well water supply installation (DTWSI) was selected as a case for the study. Computing correlation (n=30 DTWSI), the study finds small group size, high dependence on a resource system, interdependency among user groups, heterogeneity of endowments, affordability and willingness to pay, locally devised rules, monitoring users’ behavior, and public agency’s support strongly influence the variation in occurrence of collective action among the end-users of DTWSI. The study also finds effective collaboration between public agency officials and end-users is affected by trust, commitment, participatory decision- making, and transparency in the decision-making process. These findings are expected to contribute towards developing a scalable drinking water governance model and thereby ensure sustainable solutions for safe drinking water scarcity in Northwestern Bangladesh and elsewhere of similar context.Social Science Review, Vol. 40(2), December 2023 Page: 81-112